Antara Tuntutan dan Kesepakatan: BLBI dan Era Deferred Prosecution Agreement - Simanjuntak, Melva Retta Ruby; Nelson, Febby Mutiara (UI Scholars Hub, 2024)
This article discusses the settlement of criminal cases through Deferred Prosecution Agreement (“DPA”) procedures, particularly in the context of the Bantuan Likuiditas Bank Indonesia (“BLBI”) Case. The purpose of this discussion is to find a mechanism for settling criminal cases that aligns with principles of simple, fast, and cost-effective justice, especially in cases involving corporations. The focus of the article includes two aspects: the impact of using DPA mechanisms in resolving criminal cases and the impact of using DPA mechanisms in improving the efficiency of BLBI case resolution. The method used in this research is a doctrinal study focusing on research regarding rules, principles, and norms related to the settlement of criminal cases, specifically using the DPA mechanism. In the BLBI case, it is known that the case was settled through a non-criminal mechanism using the Master Settlement Acquisition Agreement (“MSAA”). MSAA is an application of the Non-Prosecution Agreement (“NPA”) mechanism because there was no involvement of Prosecutors and Courts in drafting the MSAA. If at that time the government had chosen the DPA mechanism, the settlement of the BLBI case could have been faster. This is because in DPA, Prosecutors can immediately prosecute if the party fails to comply with the terms of the agreement within the specified time. Thus, it would no longer be necessary to involve the criminal justice system process starting from the investigation stage. Keywords: Deferred Prosecution Agreement (“DPA”), BLBI case, corporations.